UPAYA PENGEMBANGAN SDM UNTUK PENINGKATAN KINERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMBA BARAT (Magister Manajemen Universitas Wisnuwardhana, 2022)
. The objectives of this research to be achieved are (1) To understand human resource development efforts to improve employee performance at the Office of Youth and Sports Education Office of West Sumba Regency (2) To understand the inhibiting factors in human resource development efforts to improve employee performance. at the Office of Education, Youth and Sports of West Sumba Regency. This type of research is qualitative research, namely research that intends to understand the phenomena of what is experienced by research subjects such as behavior, perceptions, motivations, actions and others, holistically and with a special natural context and by utilizing various natural methods. From the results of this study, it is known that several factors are instrumental in efforts to develop Human Resources (HR) to improve employee performance at the Department of Youth and Sports Education, Kab. West Sumba, among others; (1) Leadership Policy, (2) Infrastructure, (3) Infrastructure, (4) Organizational Culture, (5) Employees. Meanwhile, several obstacles in the Efforts to Develop Human Resources to Improve Employee Performance at the Office of the Youth and Sports Education Office of West Sumba Regency, among others, are as follows; (1) Lack of Human Resources owned by employees, (2) Regional Infrastructure, (3) Infrastructure for the Office of Youth and Sports Education, (4) Influence of the application of local culture, (5) Employee welfare.